Resurrection on the Road to Damascus? Exploring Paul’s Purview on His Damascus Experience - SANDNES, Karl Olav (Studia Universitatis Babeș-Bolyai Sacra Scripta, 2026)
Scholars agree that Paul's Damascus experience was life-changing, but they disagree when it comes to how that is to be defined. This article delves into the resurrection-aspects present in how Paul describes this event. Romans 4,17 about God "who gives life to the dead and calls into existence the things that do not exist" is given a bearing on Paul's experience. The grace he found in this event is resurrection at work.